Translation Process of Core Values, Vision, and Mission into The Prescribed Curriculum - Antonius Cahyono Tondoprasetyo (Beyond Words, 2022)
The case study is intended to describe how Core Values, Vision, and Mission of English Education Department in Widya Mandala Catholic University’s Graduate School (Magister Pendidikan Bahasa Inggris or “MPBI”) are translated into the syllabi (prescribed curriculum) using the Value Sharing Model as the framework and Actor Network Theory (ANT) to explain the process within this framework. The research questions are: first, do the course syllabi reflect the Vision, Mission and Core Values of MPBI? And second, how the vision, mission and core values are translated into the prescribed curriculum (syllabi)? This study was conducted by analyzing the syllabi using document analysis parameters and triangulated by conducting interviews to some lecturers and students in MPBI-19. The results are: first, the syllabi were reflecting the core values, vision and mission statements. Second, there are four ways to deliver values. Third, syllabus should be seen as a part of a curriculum not as a separated unit of course. Fourth, all courses are crystallized in Teaching Practice course (in practical term) and Thesis Writing (in theoretical form). The suggestions were: first, using a generalized format of syllabus to help lecturers state their values explicitly. Second, there are opportunities to research further the same topic in the scope of enacted curriculum. And third, lecturers should maintain their internalization processes.